Function of Armcx3 and Armc10/SVH Genes in the Regulation of Progenitor Proliferation and Neural Differentiation in the Chicken Spinal Cord - Mirra, Serena; Ulloa, Fausto; Gutierrez-Vallejo, Irene; Martì, Elisa; Soriano, Eduardo (Frontiers in Cellular Neuroscience, 2016)
The eutherian X-chromosome specific family of Armcx genes has been described as originating by retrotransposition from Armc10/SVH, a single Arm-containing somatic gene. Armcx3 and Armc10/SVH are characterized by high expression in the central nervous system and they play an important role in the regulation of mitochondrial distribution and transport in neurons. In addition, Armcx/Arm10 genes have several Armadillo repeats in their sequence. In this study we address the potential role of this gene family in neural development by using the chick neural tube as a model. We show that Armc10/SVH is expressed in the chicken spinal cord, and knocking-down Armc10/SVH by sh-RNAi electroporation in spinal cord reduces proliferation of neural precursor cells (NPCs). Moreover, we analyzed the effects of murine Armcx3 and Armc10 overexpression, showing that both proteins regulate progenitor proliferation, while Armcx3 overexpression also specifically controls neural maturation. We show that the phenotypes found following Armcx3 overexpression require its mitochondrial localization, suggesting a novel link between mitochondrial dynamics and regulation of neural development. Furthermore, we found that both Armcx3 and Armc10 may act as inhibitors of Wnt-β-catenin signaling. Our results highlight both common and differential functions of Armcx/Armc10 genes in neural development in the spinal cord.